ROBUST AND FIT-FOR-PURPOSE SAND-CONTROL TECHNOLOGY APPLICATION TO PRODUCE MARGINAL RESERVES IN PERTAMINA HULU MAHAKAM - Sobirin, Muhammad
Pertamina Hulu Mahakam (PHM) is an oil and gas exploration and production operator in Mahakam delta river. Mature fields development in Mahakam was aiming shallow unconsolidated sand-stone reservoirs with high sand-risk character. The proportion of shallow wells development is tending to increase recently. As the result, even though it contributes major part of company’s production, but it also has natural consequences on the increasing trend of sand-produced volume. Sand production is not expected and become one of the most dangerous hazard in the industry because the sand grains has abrasive physical property. It may cause consequences of a detrimental to the short-long-term well productivity, damage the hydrocarbon-contained surface facilities and may even cause a serious to catastrophic safety accident. The loss of hydrocarbon containment and release into the atmosphere might be followed by deadly disaster (fire and environment pollutions). In order to safely produce these reservoirs type, PHM currently applies the robust dieselbased chemical sand-consolidation (DB-SCON) technology for considerably high stakes